Pharmacokinetic Profiling of Ursodoxycholic Acid Using a Validated 2D-LC-MS/MS Approach (Development Engineering Conferences Center Articles Database, 2024)
This study explores the pharmacokinetic behavior of Ursodoxycholic Acid (UDCA) in human subjects using a validated two-dimensional liquid chromatography-tandem mass spectrometry (2D-LC-MS/MS) method. The method employs precise calibration and internal standardization with Valsartan, achieving consistent linearity (R² > 0.995) and low detection limits (50 ppb). Analytical method validation included tests for accuracy, reproducibility, matrix effects, and robustness, following ICH and EMEA guidelines. The validated method was applied to clinical plasma samples from volunteers receiving UDCA, providing detailed pharmacokinetic profiles over 72 hours. The results highlight the method's capability to support therapeutic drug monitoring and pharmacokinetic modeling of UDCA, emphasizing its reliability and applicability for advanced clinical research.